Child and parent outcomes following parent interventions for child emotional and behavioral problems in autism spectrum disorders: A systematic review and meta-analysis - Tarver, Joanne; Palmer, Melanie; Webb, Sophie; Scott, Stephen; Slonims, Vicky; Simonoff, Emily; Charman, Tony (Autism : the international journal of research and practice, 2019)
There is growing interest in the development of behavioral parent interventions targeting emotional and behavioral problems in children with autism spectrum disorders. Such interventions have potential to improve a number of child and parental well-being outcomes beyond disruptive child behavior. This systematic review and meta-analysis assesses evidence for the efficacy of behavioral parent interventions for disruptive and hyperactive child behavior in autism spectrum disorders, as well as parenting efficacy and stress. A total of 11 articles from nine randomized controlled trials were included. Sufficient data were available to calculate standardized mean difference and show favorable effects of behavioral parent interventions on parent-reported measures of child disruptive behavior (standardized mean difference = 0.67), hyperactivity (standardized mean difference = 0.31) and parent stress (standardized mean difference = 0.37); effects on parent efficacy are less clear (standardized mean difference = 0.39, p = 0.17). There were insufficient data to explore intervention effects on internalizing behavior in autism spectrum disorders, parenting behaviors, or observational and teacher-reported outcomes, providing important avenues for future research. This review adds to growing evidence of the efficacy of behavioral parent interventions for child behavior and parental well-being in autism spectrum disorders (Prospero: CRD42016033979).